Flow Characteristics and Grain Size Distribution of Granular Gangue Mineral by Compaction Treatment - Ran Yuan; Dan Ma; Hongwei Zhang (Advances in Materials Science and Engineering)
A test system for water flow in granular gangue mineral was designed to study the flow characteristics by compaction treatment. With the increase of the compaction displacement, the porosity decreases and void in granular gangue becomes less. The main reason causing initial porosity decrease is that the void of larger size is filled with small particles. Permeability tends to decrease and non-Darcy flow factor increases under the compaction treatment. The change trend of flow characteristics shows twists and turns, which indicate that flow characteristics of granular gangue mineral are related to compaction level, grain size distribution, crushing, and fracture structure. During compaction, larger particles are crushed, which in turn causes the weight of smaller particles to increase, and water flow induces fine particles to migrate (weight loss); meanwhile, a sample with more weight of size (0–2.5 mm) has a higher amount of weight loss. Water seepage will cause the decrease of some chemical components, where SiO2 decreased the highest in these components; the components decreased are more likely locked at fragments rather than the defect of the minerals. The variation of the chemical components has an opposite trend when compared with permeability.